Effect of omega 3 fatty acids on C-reactive protein and interleukin-6 in patients with advanced nonsmall cell lung cancer. Issue 37 (September 2018) - Lu, Yan; Chen, Ren-gang; Wei, San-zou; Hu, Han-guo; Sun, Fei; Yu, Chun-hui
Abstract : Abstract: This study investigated the anti-inflammatory effects of omega 3 fatty acids (O3FAs) for patients with advanced nonsmall cell lung cancer (ANSCLC). A total of 137 patients with ANSCLC were included in this study. Of those, 77 patients underwent O3FA and were assigned to a treatment group, while 60 patients did not receive it, and were assigned to a control group. C-reactive protein (CRP), and interleukin (IL)-6 levels, as well as the levels of tumor necrosis factor-alpha (TNFα) and prostaglandin E2 (PGE2 ) were checked. In addition, nutritional status and quality of life were also evaluated. All patients in the treatment group received a total of 6 weeks treatment. After 6 weeks treatment, patients in the treatment group exerted better outcomes in CRP and IL-6, although no significant differences were found in nutritional status, as well as the quality, compared with patients in the control group. The results of this retrospective study found that O3FA may change levels of CRP and IL-6, except the nutritional status and quality of life.